Evidence in Civil Law - Romania - Spinei, Sebastian (Law & Society, 2015)
This study is offering a review of the most important institutions of the Romanian law of evidence: the fundamental principles of civil procedure, as well as the general principles of evidence taking; an analysis of the various means of evidence, and of the rules regarding the taking of evidence; some specific issues such as the unlawful evidence, the costs, language and translation in the process of the taking of evidence, are also examined.